2009
DOI: 10.1111/j.1365-2427.2008.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource quality and stoichiometric constraints on stream ecosystem functioning

Abstract: 1. Resource quality and stoichiometric imbalances in carbon : nutrient ratios between consumers and resources can influence key ecosystem processes. In many streams, this has important implications for food webs that are based largely upon the utilization of terrestrial leaf-litter, which varies widely among litter types in its value as a food source for detritivores and as a substrate for microbial decomposers. 2. We measured breakdown rates and macroinvertebrate colonization of leaf-litter from a range of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
228
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(246 citation statements)
references
References 62 publications
15
228
1
2
Order By: Relevance
“…Our no-effect result sharpens the conclusion of Schindler and Gessner (2009) who found litter-mixture effects on decomposition to be weak. Importantly, our experimental design addressed various previously raised issues (Gessner 2010, Lecerf and, including a potential lack of statistical power to detect diversity effects, by assessing responses to litter dissimilarity within two-species mixtures on a continuous scale, based on litter chemistry traits known to affect decomposition (Melillo et al 1982, Hladyz et al 2009, Talbot and Treseder 2012.…”
Section: Effects Of Litter Trait Dissimilarity On Decompositionmentioning
confidence: 99%
“…Our no-effect result sharpens the conclusion of Schindler and Gessner (2009) who found litter-mixture effects on decomposition to be weak. Importantly, our experimental design addressed various previously raised issues (Gessner 2010, Lecerf and, including a potential lack of statistical power to detect diversity effects, by assessing responses to litter dissimilarity within two-species mixtures on a continuous scale, based on litter chemistry traits known to affect decomposition (Melillo et al 1982, Hladyz et al 2009, Talbot and Treseder 2012.…”
Section: Effects Of Litter Trait Dissimilarity On Decompositionmentioning
confidence: 99%
“…Essentially, these new ideas combine the two fundamental biological currencies of energy and matter. Again, while ES has become increasingly integral to a range of food web and ecosystem functioning studies (Elser & Hessen 2005;Hladyz et al 2009), it remains largely absent from freshwater B-EF research per se (Woodward 2009). A novel application in this context could include an additional covariate relating to the elemental ratios (i.e.…”
Section: Unifying Concepts Within a Biodiversity-ecosystem Functioninmentioning
confidence: 99%
“…Quantified measures of consumerresource C : nutrient imbalances (or mismatches) could be used to gain insight into the nutrient requirements of consumer assemblages on different resource types (e.g. Hladyz et al 2009). Potentially, such measures could then be combined with the metabolic capacity of assemblages (derived from body size and temperature scaling) to account for energetic and nutrient demands from which the strength of any residual variation explained by biodiversity effects can be assessed.…”
Section: Unifying Concepts Within a Biodiversity-ecosystem Functioninmentioning
confidence: 99%
“…The reduced consumption of DRY leaves was expected due to their lower conditioning (Cummins and Klug 1979;Graça et al 2001), the result of reduced microbial metabolism in terrestrial habitats (Molles et al 1995). Among aquatic detritivores, leaf palatability has been inversely related to leaf toughness and positively related to fungal biomass and N concentration (Irons et al 1988;Hladyz et al 2009;Aßmann et al 2011), which were significantly lower in our DRY leaves. More surprising, however, was the reduced consumption rates of Stenophylax when fed on an INT diet in comparison to the PERM diet, given the similarities between these types of leaves.…”
Section: Discussionmentioning
confidence: 96%
“…Because effects on microorganisms increase with drying duration (Langhans and Tockner 2006), changes in fungal activity or assemblage composition favouring more resistant or terrestrial species cannot be excluded. Several studies have shown that the consumption rates of shredders vary according to the fungal species in leaf assemblages (Arsuffi and Suberkropp 1984;Chung and Suberkropp 2009;Jabiol and Chauvet 2012), whereas lower microbial activity during the terrestrial phase (Langhans et al 2008;Larned et al 2010;Bruder et al 2011) might have prevented the degradation of repellent secondary metabolites or more recalcitrant C, such as cellulose, lignin or condensed tannins, resulting in increased leaf toughness and thus, less palatable leaves in the INT than PERM treatments (Irons et al 1988;Hladyz et al 2009;Graça and Cressa 2010;Aßmann et al 2011). As expected, the increased consumption of PERM leaves translated into higher growth rates, which is consistent with the bigger size at eclosion found for an insect detritivore reared on continuously submerged resources (Aspbury and Juliano 1998).…”
Section: Discussionmentioning
confidence: 99%